Optimization Existence Bumdes as Supporter Economy in Village Angantaka Badung - PUTRI, Putu Yudha Asteria; SAPUTRA, Komang Adi Kurniawan; SANTINI, Ni Made (Indonesia Strategic Sustainability, 2024)
You will experience problems or obstacles in running every business that executes suitable business trading or service. Body business owned by village Which called with BUMDes aims as mover economy village and well-being public village. Village Angantaka Regency Badung is the Wrong village That owns BUMDes as a supporter of its economy. BUMDes Chess Eka Amertha has several business units: shops, credit loans, bicycle loans, and motorcycle loans. BUMDes Chess Eka Amertha has a chance to enhance the well-being of the public village. There is still a constraint in its implementation, which is experienced and related to understanding accountancy simple and system management company. Group 33 KKN-PMM Angantaka Village in 2024 will carry out approaches and solutions to the problems associated with BUMDes governance to make BUMDes Village Angantaka an institution that stands sustainably. Activity PMM KKN consists of a presentation of a paper about orderly financial administration and corporate governance. Implementation method the activity consists of several stages: Preparation, Training, Adjustment and Evaluation. Based on the results of discussions with participants, participants were very grateful to the Warmadewa University PMM KKN Group because it can solve classic problems. Problem regarding the expected preparation of report finance: No appear Again, and accountability can be held appropriately.